High resolution imaging with SAR using automotive millimeter wave radars - Leander, Oskar; Pettersson, Viktor (My University, 2021)
Angular resolution is currently one of the main limitations in automotive radars used in advanced driver assistance systems (ADAS). This thesis investigates the pos sibility of achieving fine-resolution radar images with a commercial, off-the-shelf au tomotive radar sensor using synthetic aperture radar (SAR). Two imaging algorithms have been investigated and implemented with a Texas Instruments AWR1843 radar system, and the resulting resolution in azimuth has been compared to that of conven tional processing methods. The potential of a side-looking SAR imaging system has been investigated in the ory, in simulations and an experimental system was implemented on an actual moving vehicle. Imaging of various automotive scenarios have been performed, and the image quality of the two algorithms, backprojection and Doppler beam sharpening (DBS), has been evaluated. Simulations and measurements show that the resulting system greatly improves azimuth resolution over the conventional multiple-input multiple output (MIMO) imaging capability of the AWR1843 when in a side-looking mode of operation. The results have helped uncover potential challenges with SAR imaging, such as dynamic scenes and imperfect radar platform motion estimation. The latter problem was overcome using autofocus algorithms. In conclusion, the devised SAR system shows great promise in delivering fine az imuthal information for improving situational awareness in future ADAS functionality using today’s hardware.
Keywords: High resolution imaging with SAR using automotive millimeter wave radars, remote sensing